MOS Study Guide for Microsoft Word Exam MO-100 - Lambert, Joan (Microsoft Press, 2020)
Advance your proficiency with Word. And earn the credential that proves it! Demonstrate your expertise with Microsoft Word! Designed to help you practice and prepare for Microsoft Office Specialist: Word Associate (Word and Word 2019) certification, this official Study Guide delivers: " In-depth preparation for each MOS objective " Detailed procedures to help build the skills measured by the exam " Hands-on tasks to practice what you've learned " Ready-made practice files Sharpen the skills measured by these objectives: " Manage Documents " Insert and Format Text, Paragraphs, and Sections " Manage Tables and Lists " Create and Manage References " Insert and Format Graphic Elements EXAM MO-100 About the MOS: Associate Certification A Microsoft Office Specialist (MOS): Associate certification validates your hands-on competency in the correct application of the principal features of an Office product. It demonstrates that you can apply these features to complete associate-level tasks independently and are ready to enter the job market. See full details at: microsoft.com/learn Practice Files Available at: MicrosoftPressStore.com/MOSWord100/Downloads